Adipogenesis and insulin sensitivity in obesity are regulated by retinoid-related orphan receptor gamma - Meissburger, Bettina; Ukropec, Jozef; Roeder, Eva; Beaton, Nigel; Geiger, Matthias; Teupser, Daniel; Civan, Burcak; Langhans, Wolfgang; Nawroth, Peter Paul; Gasperikova, Daniela; Rudofsky, Gottfried; Wolfrum, Christian (EMBO molecular medicine, 2011)
Abstract Obesity is a well-known risk factor for the development of secondary complications such as type 2 diabetes. However, only a part of the obese population develops secondary metabolic disorders. Here, we identify the transcription factor retinoid-related orphan receptor gamma (ROR?) as a negative regulator of adipocyte differentiation through expression of its newly identified target gene matrix metalloproteinase 3. In vivo differentiation of adipocyte progenitor cells from Ror?-deficient mice is enhanced and obese Ror??/? mice show decreased adipocyte sizes. These small adipocytes are highly insulin sensitive, leading to an improved control of circulating free fatty acids. Ultimately, Ror??/? mice are protected from hyperglycemia and insulin resistance in the state of obesity. In adipose stromal-vascular fraction from obese human subjects, Ror? expression is correlated with adipocyte size and negatively correlated with adipogenesis and insulin sensitivity. Taken together, our findings identify ROR? as a factor, which controls adipogenesis as well as adipocyte size and modulates insulin sensitivity in obesity. ROR? might therefore serve as a novel pharmaceutical target to treat obesity-associated insulin resistance.